Vertebral Algic Syndrome Treatment in Long COVID—Cases Reports - Andrej Džubera (MDPI AG, 2021)
Though pain is a frequent symptom of long COVID-19, little attention has been paid to vertebral algic syndrome. Therefore, we present the cases reports of two precisely selected physically active patients where vertebral algic syndrome and radiculopathy dramatically worsened in acute SARS-CoV-2 infections. The vertebral pain with radicular irritation was resistant to conservative treatment in chronic post-COVID syndrome. The neurological difficulties corresponded to the radiologic imaging presented on MRI scans. Due to the absence of standard therapeutic guidelines in literature sources, it was decided to provide routine therapeutic procedures. Spinal surgery with radicular decompression was performed within 6 months after acute SARS-CoV-2 infection. This led to the improvement of their neurological status and was in corroboration with decreases of VAS (from 9 to 0 in Patient 1 and from 7 to 1 in Patient 2). Our experience indicates that these patients benefited from the standard neurosurgical radicular decompression, and sufficient pain relief was achieved; nevertheless, the initial trigger of neurological worsening was acute SARS-CoV-2 infection.